ESTIMATION OF GENERAL ABILITY, HYBRID AND GENE ACT OF FIRST AND SECOND OF GENERATION OF ONE CHARACTERS OF WHEAT GRAIN QUALITY (Triticum aestivum L.) - Ahmed, Omar. A .; Aziz, Jassem M. (Diyala Agricultural Sciences Journal, 2020)
In order to study the federal ability, hybrid power and gene action of the qualities related to the quality of the grain of wheat genotypes Triticum aestivum. (7) Milan (8) Plateaus (9) Fathers 99 (10) Cham 6) Conducted crosshalf hybridization to obtain (45) hybrids individually, planted hybrids with parents three replicates using the design RCBD for the first generation (2018 and 2019) The second generation (2019), studied the characteristics (individual plant yield and protein ratio), from the table of variance analysis showed that the average squares (genotypes, parents, hybrids and parents against hybrids) were genotypes, parents and Parents against hybrids did not reach the moral limits of the individual plant yield for all generations and second generation 2019 for protein ratio and first generation 2019 for total kidney ratio and significant in other generations for protein ratio. The two federations were less than the correct one for individual plant yield and for all generations and the first generation 2018 for protein ratio and the first and second generation 2019 for protein ratio and joint analysis. ) Is estimated General federation For the majority of traits, hybrids (1×8), (6×9), (7×10), (8×10), (2× 6) and (2×10) were of special federal capacity for the majority of traits.